2000
DOI: 10.1029/1999gb900070
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the global isotopic budget of atmospheric nitrous oxide

Abstract: Abstract. A simple box model is developed which accounts for the natural and anthropogenic sources and sinks of tropospheric nitrous oxide. Stable isotopic terms are included as well to investigate what additional insight they might provide concerning the overall picture of the global nitrous oxide budget. It is seen that fractionation associated with ultraviolet photolysis in the stratosphere plays a key role in balancing the isotopic budget. It is also noted that increased production due to human influence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 35 publications
(11 reference statements)
11
124
0
Order By: Relevance
“…The end-member mixing model was not applicable to the CS culture because of the partial oxidation of ammonia and hence the 15 N bulk -N 2 O produced by strain CS did not reflect the isotopic shifts of NH 4 þ . The ranges of d 15 N bulk -N 2 O from soil AOA were similar to those (-10 to -50%) from agricultural soils and forest soils (Kim and Craig, 1993;Rahn and Wahlen, 2000;Pérez et al, 2001;Rock et al, 2007). Previous studies found that the d 15 N bulk -N 2 O values of marine AOB (Nitrosomonas marina C-113) were about -10% with 20% O 2 concentration (Frame and Casciotti, 2010), whereas the d 15 N bulk -N 2 O values of N. europaea (ATCC 19718) in ammonia-oxidizing and nitrite-reducing conditions were -46.5% and -34.0%, respectively (Sutka et al, 2003(Sutka et al, , 2006.…”
Section: Aoa Strainsmentioning
confidence: 57%
“…The end-member mixing model was not applicable to the CS culture because of the partial oxidation of ammonia and hence the 15 N bulk -N 2 O produced by strain CS did not reflect the isotopic shifts of NH 4 þ . The ranges of d 15 N bulk -N 2 O from soil AOA were similar to those (-10 to -50%) from agricultural soils and forest soils (Kim and Craig, 1993;Rahn and Wahlen, 2000;Pérez et al, 2001;Rock et al, 2007). Previous studies found that the d 15 N bulk -N 2 O values of marine AOB (Nitrosomonas marina C-113) were about -10% with 20% O 2 concentration (Frame and Casciotti, 2010), whereas the d 15 N bulk -N 2 O values of N. europaea (ATCC 19718) in ammonia-oxidizing and nitrite-reducing conditions were -46.5% and -34.0%, respectively (Sutka et al, 2003(Sutka et al, , 2006.…”
Section: Aoa Strainsmentioning
confidence: 57%
“…4.3). The amount of air trapped within the ice sample is also used to calculate the total air content of the ice (Raynaud and Lebel, 1979). To this end, the bulk air leaving the AirTrap at −78 • C is re-collected on the air volume trap at −196 • C (SST tubing,8 cm,o.d.…”
Section: Re-collection Of the Bulk Airmentioning
confidence: 99%
“…To identify melt layers from a reduced air content caused by melting, the "background air content" of unaffected bubble ice has to be established, which is primarily a function of the altitude (Raynaud and Lebel, 1979). The third principle uses the fact that some gases are more water-soluble than other gases, producing characteristic deviations in the mixing ratios of otherwise temporally fairly constant atmospheric gas species.…”
Section: Xe Air Ratio As Melt Layer Proxymentioning
confidence: 99%
See 2 more Smart Citations